2004
DOI: 10.1530/rep.1.00204
|View full text |Cite
|
Sign up to set email alerts
|

Insulin acts via mitogen-activated protein kinase phosphorylation in rabbit blastocysts

Abstract: The addition of insulin during in vitro culture has beneficial effects on rabbit preimplantation embryos leading to increased cell proliferation and reduced apoptosis. We have previously described the expression of the insulin receptor (IR) and the insulin-responsive glucose transporters (GLUT) 4 and 8 in rabbit preimplantation embryos. However, the effects of insulin on IR signaling and glucose metabolism have not been investigated in rabbit embryos. In the present study, the effects of 170 nM insulin on IR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 62 publications
(49 reference statements)
0
9
0
2
Order By: Relevance
“… H2AFZ : H2A histone family member Z [35]; GAPDH : glyceraldehyde-3-phosphate dehydrogenase [36]; SMARCA2 : SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily a, member 2; EMP1 : Epithelial membrane protein 1; CALC : calcitonin gene-related peptide variant 1; SCGB1A1 : secretoglobin family 1A member 1).…”
Section: Methodsmentioning
confidence: 99%
“… H2AFZ : H2A histone family member Z [35]; GAPDH : glyceraldehyde-3-phosphate dehydrogenase [36]; SMARCA2 : SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily a, member 2; EMP1 : Epithelial membrane protein 1; CALC : calcitonin gene-related peptide variant 1; SCGB1A1 : secretoglobin family 1A member 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to indirect effects of EDCs on embryo development, exerted via changes in hormone profiles, direct embryotoxic effects are possible through actions of EDCs on hormone receptors (Agras et al ., 2007; Davey et al ., 2007). It has been shown that the hormone receptor expression in blastocysts differs between embryoblast and trophoblast, which represent different cell lineages, and this results in different developmental impacts (Navarrete Santos et al ., 2004a, 2004b and 2008). Along with steroid hormone receptors, many of the effects of EDCs on pre-implantation embryos, and on implantation, are mediated through the aryl hydrocarbon receptor (AhR) and peroxisome proliferator-activated receptor (PPAR) signalling pathways.…”
Section: Effects On Animal Physiologymentioning
confidence: 99%
“…In diabetes, insulin has been shown to induce proliferation of vascular smooth muscle cells, suggesting that insulin might be involved in the progression of atherosclerosis [18]. Another study, performed on rabbit blastocysts, also showed that insulin functions as a growth‐inducing factor without affecting glucose transport [19]. Thus, insulin has the ability to function as a mitogen in a number of different cell types, and therefore could be directly involved in the complications associated with the diabetic condition.…”
Section: Discussionmentioning
confidence: 99%